The Impact Of Introducing Brown Gas Into The Incoming Air Flow On The Performance Of An Internal Combustion Engine - Wahyu, Mujahid; Susilo, Sugeng Hadi; Kamal, Dianta Mustofa (Politeknik Negeri Lhokseumawe, 2024)
The increase in the number of motorized vehicles has led to challenges in maintaining environmental air quality, combustion efficiency, and the sustainability of fossil fuels. An innovative solution to address these issues is the utilization of brown gas. This study aims to investigate the impact of introducing brown gas into the incoming air flow on the performance of an internal combustion engine. The brown gas flow rate varies based on the gas production rate resulting from variations in the addition of NaOH (10 g/l, 20 g/l, and 30 g/l) to every 1 liter of water in the generator. Gas production rates are measured using a flow meter. The influence of brown gas on gasoline engine performance is assessed through power testing with a chassis dyno test engine and exhaust emissions testing with a gas analyzer. The findings reveal that the highest flow rate of brown gas is achieved with the addition of 30 g/l NaOH during the electrolysis process. Introducing brown gas into the incoming air flow can increase maximum engine power by 15.5% and reduce CO exhaust emissions by 23.37%.